THE COMPARISON BETWEEN INTEGRATED AUDIO MEDIA OF YA LAL WATHAN AND POWER POINT MEDIA ON THE STUDENT'S COGNITIVE ABILITY - Ana Reni Ratna Wati; Ruswan Ruswan; Hafidha Asni Akmalia (Indonesian Journal of Science and Education (IJOSE), 2021)
The use of instructional media is one of the teacher's efforts to create maximum teaching and learning processes. Research on the use of integrated audio media Ya Lal Wathan in this study was carried out because the media used were new and had never been used by previous studies. This study aims to compare the effect of Ya Lal Wathan's integrated audio media and power point media on the cognitive abilities of high school students on Kingdom Plantae material. The study design used the Non-equivalent Control Group Design using a purposive sampling technique. We took all of students in MAN 1 Semarang as population and 2 classes as sample. The instruments used were 20 pre-test questions and 20 post-test questions given in power point and integrated audio class. Data were analyzed by Sign Test. The result of the study showed that there was an equally significant effect between two classes. However, students taught by integrated audio got an average grade in the post-test that is higher than the control class so there is a positive tendency that integrated audio media with Ya Lal Wathan is good for application in learning. It is necessary to innovate our audio media for further research.